2D Ultrathin MXene‐Based Drug‐Delivery Nanoplatform for Synergistic Photothermal Ablation and Chemotherapy of Cancer. Issue 9 (5th February 2018) - Han, Xiaoxia; Huang, Ju; Lin, Han; Wang, Zhigang; Li, Pan; Chen, Yu
Abstract: Two‐dimensional (2D) MXenes, as a new 2D functional material nanosystem, have been extensively explored for broad applications. However, their specific performance and applications in theranostic nanomedicine have still rarely been explored. This work reports on the drug‐delivery performance and synergistic therapeutic efficiency of Ti3 C2 MXenes for highly efficient tumor eradication. These Ti3 C2 MXenes not only possess high drug‐loading capability of as high as 211.8%, but also exhibit both pH‐responsive and near infrared laser‐triggered on‐demand drug release. Especially, based on the high photothermal‐conversion capability of Ti3 C2 MXenes, they have been further explored for efficient tumor eradication by synergistic photothermal ablation and chemotherapy, which has been systematically demonstrated both in vitro and in vivo. These Ti3 C2 MXenes have also been demonstrated as the desirable contrast agents for photoacoustic imaging, showing the potential for diagnostic‐imaging guidance and monitoring during therapy. The high in vivo histocompatibility of Ti3 C2 and their easy excretion out of the body have been evaluated and demonstrated, showing the potential high biosafety for further clinical translation. This work paves a new way for broadening biomedical applications of MXenes in nanomedicine where they can exert the high performance and functionality for synergistic therapy, especially on combating cancer. Abstract : Two‐dimensional (2D) Ti3 C2 MXene‐based nanosheets have been successfully constructed for controllable drug releasing and synergistic photothermal hyperthermia/chemotherapy against cancer. Especially, based on the high photothermal‐conversion capability of 2D Ti3 C2 MXenes, they have been further explored for highly efficient tumor eradication by synergistic Ti3 C2 ‐assisted photothermal ablation and chemotherapy, which has been systematically demonstrated both in vitro and in vivo.